Proceedings of the 2015 International Conference on Modeling, Simulation and Applied Mathematics 2015
DOI: 10.2991/msam-15.2015.55
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Temperature on the Nanoparticles Agglomerates Fluidization

Abstract: Abstract-The effect of temperature on the fluidization behavior of nanoparticles agglomerates in a fluidized bed was investigated. Moreover, a model was developed based on the force balance between drag, collision, buoyancy and gravitational forces as separation forces and van der Waals force as the attractive force. Results showed that the size of agglomerates decrease by increasing the gas velocity at constant temperature. In addition, the minimum fluidization velocity and the agglomerate size increase with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…However, viscosity augmented as a function of nanoparticle concentration; an increase of up 36 per cent in viscosity at 75°C for the highest nanoparticle concentration (0.1 wt.%). Nanoparticles tend to agglomerate due to their high surface activity (Singh et al , 2015) and interparticle forces such as van der Waals (Issa et al , 2014; Shima et al , 2010; Taha-Tijerina et al , 2014) particularly when subjected to high temperatures and/or high concentrations (Esmailpour et al , 2015). It has been demonstrated (Nisha and Philip, 2013) that nanoparticles form fractal-like clusters or agglomerates throughout the nanofluid, percolating thermal energy along them.…”
Section: Resultsmentioning
confidence: 99%
“…However, viscosity augmented as a function of nanoparticle concentration; an increase of up 36 per cent in viscosity at 75°C for the highest nanoparticle concentration (0.1 wt.%). Nanoparticles tend to agglomerate due to their high surface activity (Singh et al , 2015) and interparticle forces such as van der Waals (Issa et al , 2014; Shima et al , 2010; Taha-Tijerina et al , 2014) particularly when subjected to high temperatures and/or high concentrations (Esmailpour et al , 2015). It has been demonstrated (Nisha and Philip, 2013) that nanoparticles form fractal-like clusters or agglomerates throughout the nanofluid, percolating thermal energy along them.…”
Section: Resultsmentioning
confidence: 99%
“…It is noteworthy that the contact angle measurements were conducted at 25 °C and the amounts of asphaltenic deposition generated from the microreactor and flow loop were obtained using a test temperature of >85 °C and in the presence of pressure. However, it is reported that LW interactions increase with the temperature, , EL interactions do not vary much with the temperature, and Lewis acid–base interaction parameters decrease inversely with the temperature . On the basis of this information, the Lewis acid–base interactions are negligible compared to LW and EL interactions at high temperatures.…”
mentioning
confidence: 90%
“…The agglomeration transforms individual nanoparticles into combined nanoparticles. The combination of nanoparticles substantially increases the average size [132,133]. The increase in average size hinders the entry of these particles at the surface interactions.…”
Section: Temperaturementioning
confidence: 99%